Contemporary research methods in hospitality and tourism - Okumus, Fevzi; Rasoolimanesh, S. Mostafa; Jahani, Shiva (Emerald Publishing Limited, 2022)
The hospitality and tourism industry is one of the fastest growing industries worldwide, with a contribution of 9% to world GDP and 10% of job creation. The fast pace of growth in this industry highlights the importance of applied and pure research studies to address the theoretical and practical problems which the industry faces daily from economic, social, cultural, environmental, political, and technological perspectives. New understanding of both new and traditional research paradigms in the context of tourism and hospitality is vital to strengthen the research culture and find more accurate and reliable solutions for emerging problems. Contemporary Research Methods in Hospitality and Tourism delivers a comprehensive collection of chapters including new insights for traditional paradigms, approaches, and methods, as well as more recent developments in research methodology in the context of tourism and hospitality. Each chapter connects the discussed approach or method to tourism and hospitality with providing illustration examples. This volume provides an essential resource for academics, undergraduate and graduate researchers, libraries, executives, and practitioners to understand different aspects of research methodology.